Nested variant of urothelial carcinoma of renal pelvis – a case report - Kuzaka, Piotr; Pastewka, Krzysztof; Faryna, Jan; Kuzaka, Bolesław; Pypno, Wojciech; Wejman, Jarosław (Polish Journal of Pathology, 2014)
We report a case of an 80-year-old woman with a very rare subtype of urothelial carcinoma – nested variant of urothelial carcinoma mimicking physiological von Brunn’s nests. Optimal treatment of NVUC has not been determined due to the small number of cases, as well as the lack of randomized and follow-up studies. In our case the right retroperitoneal nephroureterectomy was chosen.